Diese Präsentation wurde erfolgreich gemeldet.

Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
×

1 von 1 Anzeige

# f(x)-(x^2-1)-(x-2)Solution f(x) - (x^2 - 1)^3 f -'.docx

f(x)=(x^2-1)/(x-2)
Solution
f(x) = (x^2 - 1)^3 f \' (x) = 3(x^2 - 1)^2 * 2x = 6x(x^2 - 1)^2 f \" (x) = 6(x^2 - 1)^2 + 12x(x^2 - 1)*2x = 6(x^2 - 1)^2 + 24x(x^2 - 1) f \' = 0 when x = 0 , 1 , or -1 a) f is increasing when f \' (x) > 0 using a sign chart, f \' > 0 on the intervals: (0 , 1) U (1 , inf) at x = 1, f \' is 0 b) there is only one relative min-- at x = 0 --, and no relative maxes the zeros of f \' at -1 and 1 are horizontal tangents, but not min or max c) the graph is concave up when f \" > 0 f \" (x) = 6(x^2 - 1)^2 + 12x(x^2 - 1)*2x = 6(x^2 - 1)^2 + 24x(x^2 - 1) f \" (x) = (x^2 - 1)[6(x^2 - 1) + 24x] f \" (x) = (x - 1)(x + 1)(6x^2 + 24x - 6) f \" (x) = 6(x - 1)(x + 1)(x^2 + 4x - 1) points of inflection at x = 1, -1 , [-4 +/- sqrt(20)] / 2 points of inflection: x = -1 , -2 - sqrt(5) , -2 + sqrt(5) , 1 concave up on intervals (using sign charts): (-inf , -1) U (-2 - sqrt(5) , -2 + sqrt(5)) U (1 , inf)
.

f(x)=(x^2-1)/(x-2)
Solution
f(x) = (x^2 - 1)^3 f \' (x) = 3(x^2 - 1)^2 * 2x = 6x(x^2 - 1)^2 f \" (x) = 6(x^2 - 1)^2 + 12x(x^2 - 1)*2x = 6(x^2 - 1)^2 + 24x(x^2 - 1) f \' = 0 when x = 0 , 1 , or -1 a) f is increasing when f \' (x) > 0 using a sign chart, f \' > 0 on the intervals: (0 , 1) U (1 , inf) at x = 1, f \' is 0 b) there is only one relative min-- at x = 0 --, and no relative maxes the zeros of f \' at -1 and 1 are horizontal tangents, but not min or max c) the graph is concave up when f \" > 0 f \" (x) = 6(x^2 - 1)^2 + 12x(x^2 - 1)*2x = 6(x^2 - 1)^2 + 24x(x^2 - 1) f \" (x) = (x^2 - 1)[6(x^2 - 1) + 24x] f \" (x) = (x - 1)(x + 1)(6x^2 + 24x - 6) f \" (x) = 6(x - 1)(x + 1)(x^2 + 4x - 1) points of inflection at x = 1, -1 , [-4 +/- sqrt(20)] / 2 points of inflection: x = -1 , -2 - sqrt(5) , -2 + sqrt(5) , 1 concave up on intervals (using sign charts): (-inf , -1) U (-2 - sqrt(5) , -2 + sqrt(5)) U (1 , inf)
.

Anzeige
Anzeige

## Weitere Verwandte Inhalte

Anzeige

### f(x)-(x^2-1)-(x-2)Solution f(x) - (x^2 - 1)^3 f -'.docx

1. 1. f(x)=(x^2-1)/(x-2) Solution f(x) = (x^2 - 1)^3 f ' (x) = 3(x^2 - 1)^2 * 2x = 6x(x^2 - 1)^2 f " (x) = 6(x^2 - 1)^2 + 12x(x^2 - 1)*2x = 6(x^2 - 1)^2 + 24x(x^2 - 1) f ' = 0 when x = 0 , 1 , or -1 a) f is increasing when f ' (x) > 0 using a sign chart, f ' > 0 on the intervals: (0 , 1) U (1 , inf) at x = 1, f ' is 0 b) there is only one relative min-- at x = 0 --, and no relative maxes the zeros of f ' at -1 and 1 are horizontal tangents, but not min or max c) the graph is concave up when f " > 0 f " (x) = 6(x^2 - 1)^2 + 12x(x^2 - 1)*2x = 6(x^2 - 1)^2 + 24x(x^2 - 1) f " (x) = (x^2 - 1)[6(x^2 - 1) + 24x] f " (x) = (x - 1)(x + 1)(6x^2 + 24x - 6) f " (x) = 6(x - 1)(x + 1)(x^2 + 4x - 1) points of inflection at x = 1, -1 , [-4 +/- sqrt(20)] / 2 points of inflection: x = -1 , -2 - sqrt(5) , -2 + sqrt(5) , 1 concave up on intervals (using sign charts): (-inf , -1) U (-2 - sqrt(5) , -2 + sqrt(5)) U (1 , inf)